2020
DOI: 10.3892/ol.2020.11731
|View full text |Cite
|
Sign up to set email alerts
|

Comparing human epidermal growth factor receptor 2 amplification and expression using immunohistochemistry and silver in situ hybridisation in gastric carcinoma and lymph node metastasis

Abstract: Detecting the amplification and expression of human epidermal growth factor receptor (HER2) is important for planning trastuzumab treatment for patients with gastric carcinoma. The present study aimed to analyse HER2 amplification and expression in primary gastric adenocarcinoma tumours and metastatic lymph nodes using microarray methods, and to assess the potential contribution of these methods to treatment planning. In total, 60 patients with lymph node metastasis were included in the present study. Microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Tubular adenocarcinoma (22 of the 50 cases), papillary adenocarcinoma (3 of the 50 cases), poorly cohesive carcinoma (2 of the 50 cases, including signet ring carcinoma), mucinous adenocarcinoma (3 of the 50 cases), mixed adenocarcinoma (2 of the 50 cases), and carcinoma with lymphoid stroma were used to describe these cases histologically (1 of the 50 cases). This was consistent with a study conducted by Gulten et al [15]. Around 47% of cases were tubular adenocarcinoma, 5% papillary adenocarcinoma, 35% poorly cohesive carcinoma, 10% mucinous adenocarcinoma, 3% mixed adenocarcinoma, and 4% undifferentiated cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Tubular adenocarcinoma (22 of the 50 cases), papillary adenocarcinoma (3 of the 50 cases), poorly cohesive carcinoma (2 of the 50 cases, including signet ring carcinoma), mucinous adenocarcinoma (3 of the 50 cases), mixed adenocarcinoma (2 of the 50 cases), and carcinoma with lymphoid stroma were used to describe these cases histologically (1 of the 50 cases). This was consistent with a study conducted by Gulten et al [15]. Around 47% of cases were tubular adenocarcinoma, 5% papillary adenocarcinoma, 35% poorly cohesive carcinoma, 10% mucinous adenocarcinoma, 3% mixed adenocarcinoma, and 4% undifferentiated cancer.…”
Section: Discussionsupporting
confidence: 93%
“…In one study, the sensitivity and specificity of the SISH method were reported as 56% and 100%, respectively, and the false-negative rate was 44%, according to the IHC method. These findings indicate that false negativity is very high in the SISH method, which is consistent with the findings of our study [51]. Studies investigating the relationship between clinicopathological features and HER2 expression have reported a close relationship between HER2 overexpression and gender, tumor differentiation, tumor location, tumor invasion, TNM stage, lymph node metastasis, and Lauren classification [48,50,52,53].…”
Section: Discussionsupporting
confidence: 92%